Jewish Religious and Philosophic Thought through the Lens of Analytical Philosophy - V. V. Sleptsova (Концепт: философия, религия, культура, 2022)
The reviewed Jewish Philosophy in an Analytic Age is a unique collection of essays that combine analytical philosophy to the Jewish religion. Analytical approach has been widely applied to Christianity since the 1980s and marked the legitimization of analytical philosophy of religion. This turn is primarily associated with the names of Alvin Plantinga, Richard Swinburne and others. At the same time the texts by Jewish religious philosophers are rarely, if ever, considered through the prism of analytical philosophy of religion and analytical theology. This collection of essays is not only valuable because of its exceptional nature: the authors of the essays touch upon important topics of religious philosophy, such as the correlation of the freedom of choice and a divine knowledge of the future, the epistemological distinction of faith and belief, moral justification for lying, the problem of evil, etc. The extensive Discussion part, written by Tzvi Novick from the Theology Department of the University of Notre Dame, presents the author’s attitude towards the approach taken in the book. Readers are encouraged to think of the very essence of Jewish philosophy and possibly review its understanding. The analytical approach found in the essays sometimes transcends the boundaries of the analytical philosophy of religion, contributes to the modernization of Jewish religious and philosophical works, and introduces these texts to the domain of modern analytical philosophy. The latter is achieved through analytical generalization of Jewish texts, making them universal. The abovementioned features make the book worth reading by scholars, researches, and all those interested in the modern philosophy and the study of Jewish religion.